Filmed Ethnography or Ethnographic Film? Voice and Positionality in Ethnographic, Documentary, and Feminist Film - Sikand, Nandini (Journal of film and video, 2015)
[...]a critique of disciplinary methods and boundaries deeply affected the study of anthropology and ethnographic film such that the study of anthropology, a "bourgeois discipline" (Asad 17), became entwined with how the Third World subject is understood. [...]I suggest we blur the line not simply between subject and filmmaker, but between subject, filmmaker, and audience.